Ideológiai válaszutak a két világháború közötti csehszlovákiai magyar ifjúság körében - Bajcsi, Ildikó (Per Aspera ad Astra, 2020)
This study deals with the ideological movements of the Hungarian minority intelligentsia in Czechoslovakia between the two World Wars. The process of organizing the first generation of minorities sheds light on the ideological responses that have mostly determined the life path of the young generation who have largely been socialized in Czechoslovakia. The discussed youth movements started from Scouting groups and were organized within the frameworks of veteran Scouting organizations formed around universities. Hungarian youth in Czechoslovakia, within these intellectual communities, considered handling social responsibilities and problems as a key task in creating their identity as a minority. The most important ideological group was the leftist “Sarló” (Sickle) movement, which was founded in 1928. They considered building a leftist, socialist oriented intellectual generation to be their most important task. The Prohászka Circles, formed in 1930, were also formed along the lines of socialist thought and operated on the basis of Christian socialism. Founded in 1932, the Hungarian Workshop (Magyar Munkaközösség), like the two movements above, were defined by socialistic and nationalistic values and gathered the Hungarian youth in Czechoslovakia on those foundations. By the mid-1930s the movements suffered from symptoms of ideological detachment in their leadership which caused their early initial dynamics to subside among the youth. In the second half of the 1930s the focus also shifted in favour of “national closure” and the creation of an unified Upper Hungarian identity. Photo: dunszt.sk